Appendiceal tumours – A correlation of CT features and histopathological diagnosis. Issue 1 (17th September 2021) - Brassil, Michael; Lee, Ronan; O'Neill, Damien; Woods, Graham; Moloney, Brian M; Dunne, Ruth; Morrin, Martina; Lee, Michael J
Abstract: Appendiceal tumours are uncommon neoplasms of the gastrointestinal tract. An understanding of the imaging appearances facilitates an accurate radiological description, which guides surgical and oncological management. In this study, a retrospective review of the CT imaging and histopathology of all cases of appendiceal tumours discussed at the oncology multidisciplinary meetings in a single centre, over an 8‐year period (2012–2019) is performed. The array and incidence of both common and rare pathologies are investigated, and important characteristic imaging findings for radiologists to recognize are highlighted.